2019
DOI: 10.1021/acsphotonics.9b00802
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Silicon Nanocrystals for Color-Neutral and Transparent Luminescent Solar Concentrators

Abstract: One of the most detrimental loss mechanisms in Luminescent Solar Concentrators (LSCs) is reabsorption of emitted light from the luminophore. Silicon Nanocrystals (SiNCs) offer a solution due to the high apparent Stokes shift, but the poor absorption properties limit their performance as LSC luminophores. Coupling an organic dye to SiNCs represents a smart approach to obtain sensitization of SiNC luminescence by the organic dyes, thus, resulting in tunable and improved optical properties of LSCs. In particular,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 41 publications
3
82
0
Order By: Relevance
“…With a G = 2.6, these results correspond to C = 0.11 or 1.65 based on absorbed light. [163] Thinfilm LSCs of Si QDs in PMMA deposited on glass by doctor blade have been investigated. Quick solidification of PMMA leads to low light-scattering films with an order of magnitude higher QD weight fraction than previously reported nonscattering bulk-polymerized Si QD/PMMA nanocomposites.…”
Section: Emitters Based On Qds and Nanocrystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…With a G = 2.6, these results correspond to C = 0.11 or 1.65 based on absorbed light. [163] Thinfilm LSCs of Si QDs in PMMA deposited on glass by doctor blade have been investigated. Quick solidification of PMMA leads to low light-scattering films with an order of magnitude higher QD weight fraction than previously reported nonscattering bulk-polymerized Si QD/PMMA nanocomposites.…”
Section: Emitters Based On Qds and Nanocrystalsmentioning
confidence: 99%
“…[167] The toxicity of classical QDs containing metals such as Cd or Pb has triggered the search for alternative nanomaterials as emitters. Besides the already discussed silicon QDs, [158,160,163,164] several groups have investigated CDs as possible nontoxic emitters. [161,[168][169][170][171][172][173][174][175][176] Zhou et al prepared CDs modified by a treatment with oleylamine in order to reduce absorption in long wavelengths, and thus, SA.…”
Section: Emitters Based On Qds and Nanocrystalsmentioning
confidence: 99%
“…33 Recently, SiNc with attached diphenyl anthracene were used to improve optical properties of luminescent solar concentrators utilizing SiNc PL. 34 In our previous work, we have demonstrated that microwave-assisted hydrosilylation (MAH) method can produce SiNc exhibiting a PLQY of up to 40% and excellent long-term stability (6 months without decrease of PLQY). 35 In this article, we describe an approach to attach functional dyes to the core of SiNc via hydrosilylation reaction using a microwave (MW) reactor.…”
Section: Introductionmentioning
confidence: 99%
“…5 Silicon-based QDs are attractive for many applications because they are heavy metal-free, comprised of earth-abundant elements, and biologically compatible. In this context, a variety of methods have been developed to prepare and functionalize these promising materials [6][7][8][9][10][11] and prototype applications including light-emitting diodes, 12 luminescent solar concentrators (LSCs), 13,14 biological imaging agents, 15,16 sensors, 17,18 and lithium ion battery anodes 19,20 have appeared. Many of these uses rely on the unique tailorable optical properties of SiQDs; for example, LSCs take advantage of the large Stokes shift (i.e., the energy difference between excitation and photoluminescence maxima) that arises in part because of the indirect nature of the Si band gap.…”
mentioning
confidence: 99%
“…Many of these uses rely on the unique tailorable optical properties of SiQDs; for example, LSCs take advantage of the large Stokes shift (i.e., the energy difference between excitation and photoluminescence maxima) that arises in part because of the indirect nature of the Si band gap. 13,14 Despite impressive advances including spectral tuning throughout the full visible region and photoluminescence (PL) quantum yields rivaling that of compound semiconductor QDs, challenges remain; [21][22][23][24][25] paramount among these is the limited predictability of the PL maximum size dependence that appears throughout the literature. 26 The origin of SiQD PL is clearly complex; [27][28][29][30][31][32] for convenience, SiQDs can be categorized into two broad groupings based upon PL properties and associated excited-state lifetimes.…”
mentioning
confidence: 99%